Peran Manajemen Modal Usaha dalam Keberlanjutan Warung Makan - Dinda Putri Adila; Tri Maryani (Mahesa Research Center, 2026)
This article aims to analyze the role of working capital management in supporting the sustainability of Bu Ani Food Stall. The study focuses on how capital management practices, including cash management, inventory control, accounts receivable, and short-term liabilities scheduling, affect operational continuity, profitability, and customer satisfaction. The study employs the theoretical framework of working capital and business sustainability in culinary SMEs. Data were collected through in-depth interviews with owners, employees, suppliers, and customers, direct observation, and daily financial documentation, and then analyzed qualitatively using thematic analysis. The study concludes that capital management plays a central role in sustaining the stall's operations. The owner acts as the main controller of capital, supported by employees and suppliers to ensure the availability of raw materials and smooth cash flow. Key challenges include demand fluctuations, limited reserve capital, and complex inventory management. Overall, effective capital management practices enable the stall to maintain operations, adapt to market dynamics, and serve as a model for other culinary SMEs